ASSESSMENT OF WATER QUALITY AND PHYSICOCHEMICAL PROPERTIES OF THE ALA RIVER, SOUTH WEST NIGERIA - Olorunda, Febisola Temitope; Enemali, Mathias Ojochide; Odipe, Oluwaseun Emmanuel; Adesiyan, Ibukun Modupe (FUDMA Journal of Sciences, 2026)
The Ala River, a freshwater body flowing through Akure, southwestern Nigeria, faces growing anthropogenic pressure. The study provides a comprehensive evaluation of its physicochemical characteristics and overall pollution status to determine its suitability for domestic and ecological use. Surface water samples were obtained from five strategic locations, Ala Elefosan, Oke Ijebu, Fiwasaye, Araromi, and Isinkan using the grab sampling technique. Physicochemical parameters, including pH, turbidity, electrical conductivity (EC), dissolved oxygen (DO), biochemical oxygen demand (BOD), total dissolved solids (TDS), major ions, and nutrients, were analyzed following the APHA (2017) standard procedures. The Nemerow Pollution Index (NPI) was applied to assess contamination levels, and data were statistically evaluated using ANOVA. The pH (6.9–7.4) remained within WHO and NSDWQ guidelines, indicating near-neutral water conditions. However, elevated concentrations of BOD (14.04–25.03mg/L) magnesium (15.65–36.94 mg/L), potassium (14.6–46.4 mg/L), ammonia (2.5–2.7 mg/L), and nitrates (46.1 mg/L) surpassed permissible limits at all the five selected sites. NPI values further identified magnesium (at all sites except Ala Elefonsan) and nitrate (at Isinkan) as key pollutants. Although ANOVA results (p = 0.987) revealed no significant spatial variation, consistent exceedances highlight localized contamination hotspots. The study contributes original baseline data on Ala River water quality, offering scientific evidence for future monitoring and remediation strategies. While the contamination levels are not yet alarming, the study indicates the presence of pollutants that could pose long-term risks. Hence the need for improved wastewater control and policy.
Keywords: Ala River; Physicochemical properties; Nemerow Pollution Index; Akure; Urban runoff; Anthropogenic pollution